Organizational justice and extra role behavior: examining the relationships in Malaysian cultural context - Hassan, Arif (2007)
The study examined role of organizational justice in promoting extra role behavior (ERB) in Malaysia. ERB is defined as discretionary behavior that goes beyond existing role expectations that benefit the organization. Literature on the subject indicated that social and cultural values moderate the relationship between organizational justice and organizational outcomes such as ERB. Previous studies examining the social values and culture of Malaysia have recognized this country as collectivistic and high on power distance. The study, therefore, explored two opposing hypotheses based on the cultural characteristics—one suggesting strong and another week relationship between organizational justice and ERB. A sample of 81 managerial and non managerial employees from a mix of organizations participated in the study. Data were collected using standardized questionnaires measuring study variables. Results suggested that among the four facets of organizational justice, distributive justice significantly promoted help dimension of ERB and procedural justice did the same for voice as the ERB factor. Role of two other organizational justice factors, i.e., interactional and informational justice was insignificant. The result of the study may be useful to companies operating in Malaysia who wish to promote extra role behavior among employees.